Two genetic variants in NEXN and ABCC6 genes found in a patient with right coronary artery to right ventricle fistula combined with giant coronary aneurysm and patent ductus arteriosus - Peng, Yongxuan; Ye, Jiajun; Xu, Yuejuan; Huang, Jihong; Wu, Yurong; Liu, Wei; Bai, Kai; Chen, Sun; Lu, Yanan (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Background: Coronary artery fistula is a relatively rare anomaly with an estimated incidence of 0.002% of the general population. It could combine with a giant coronary artery aneurysm with an incidence of 5.9%. The pathogenesis of these two anomalies is not clear, genetic abnormalities might be implicated in the rare anomalies. Method: One six-years old patient, with the diagnosis of right coronary artery to right ventricle fistula combined with giant right coronary artery aneurysm and patent ductus arteriosus, accepted surgical repair recently in our center. His diagnosis was affirmed by echocardiaography, CT and surgery. DNA was extracted from the peripheral venous blood sample of the patient and his mother when we got the informed consent. HE and Alizarin red staining was performed in the excised coronary artery aneurysm. Exome sequencing and in silico analysis was carried out to detect the detrimental genetic variants. Results: No obvious abnormality were found in the excised coronary artery aneurysm by HE staining and Alizarin red staining. A heterozygous truncated variant (NM_144573: c.G298T; p.G100X) in the NEXN gene and a missense variant (NM_001171: c.G1312A; p.V438M) in ABCC6 gene carried by the patient were observed but not his mother. Conclusions: NEXN truncated variant NEXN-G100X may be associated with the development of coronary artery and the congenital coronary artery anomalies.